Socio-Epidemiological Parameters Influencing the Treatment Outcome in Newly Diagnosed Smear Positive Cases Under Dots in District Amritsar - Nagpal, Manisha; Devgun, Priyanka (National Journal of Community Medicine, 2013)
Introduction: Tuberculosis has brought untold miseries to generations and even today, when newer modalities for diagnosis and treatment have made the disease curable, people are still suffering and dying from this disease. The present study is an attempt to know about the socio-epidemiological parameters affecting the treatment outcome in new smear positive patients under DOTS. Methods: The study was conducted on new smear positive patients registered under DOTS in two Treatment Units (TUs) present in Amritsar city. House to house visits were done and socio-epidemiological parameters were studied by completing a pre designed proforma evolved for this purpose. Results: Out of 250 patients, 149 (59.6%) were males and 101(40.4%) were females. 75.8% of the cases among males and 87.2% among females were in the age group of 15-45 years. Male preponderance, with male to female ratio of 1.5:1 was seen. Socio-demographic factors affecting the treatment outcome were age, sex and marital status. Conclusion: On statistical analysis, it was observed that favourable outcome was significantly associated with mean age of 29.2 ± 13.3 years (p = 0.013), female sex (OR = 2.19, p = 0.04) and unmarried cases (χ2 = 7.186, p = 0.027). Family size, literacy status and socio-economic status were not significantly associated with the treatment outcome.